1995
DOI: 10.1002/bit.260460209
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of nitrate and nitrite in a cyclically operated continuous biological reactor

Abstract: Biological reduction of nitrate and nitrite was studied with a continuously operated cyclic reactor. The medium was fed to the reactor during the first phase of the cycle, and the effluent was drawn from the reactor during the third phase of the cycle; reaction occurred throughout the cycle. The process was described mathematically based on kinetic expressions revealed in an independent study. The model equations were subjected to detailed analysis with numerical codes based on the bifurcation theory for force… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
2

Year Published

1995
1995
2004
2004

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 11 publications
0
6
0
2
Order By: Relevance
“…While in waste water treatment the required carbon source is often present in sufficient amounts, denitrification of ground water requires an addition of a carbon source. Previous research on carbon source-supported denitrification demonstrated successful nitrate removal when using a variety of carbon sources such as acetate [1], glucose [2], ethanol [3][4][5], methanol [6,7], and sawdust [8]. While mechanisms of nitrate removal are similar when using different substrates, the various groups of microorganisms present in the aquifer will differ in substrate affinity, thus denitrification rates and carbon source requirements will be influenced by the choice of substrate.…”
Section: Introductionmentioning
confidence: 96%
“…While in waste water treatment the required carbon source is often present in sufficient amounts, denitrification of ground water requires an addition of a carbon source. Previous research on carbon source-supported denitrification demonstrated successful nitrate removal when using a variety of carbon sources such as acetate [1], glucose [2], ethanol [3][4][5], methanol [6,7], and sawdust [8]. While mechanisms of nitrate removal are similar when using different substrates, the various groups of microorganisms present in the aquifer will differ in substrate affinity, thus denitrification rates and carbon source requirements will be influenced by the choice of substrate.…”
Section: Introductionmentioning
confidence: 96%
“…Analyses. NO 2 and NO 3 were quantified by denitrification by capillary electrophoresis (Millipore CIA 4000 in a melt silica column with 75 µm ID and 60 cm long at 30 mA and 20 kV (Wang et al, 1995).…”
Section: Methodsmentioning
confidence: 99%
“…The organism used in all experiments was Pseudomonas denitrificans ATCC 13867. The medium used was a modified version of that previously described (11). The base mixture consisted of 1.5 g of KH2-PO4, 5 g of K2HPO4, 5 g of NaCl, 0.06 g of CaCl2, 0.2 MgSO4‚ H2O, 2.207 g of glutamic acid, and 0.05-0.1 mL of a trace elements solution dissolved in 1 L of distilled water.…”
Section: Methodsmentioning
confidence: 99%